TP004/#1457 Trial in progress of engot-CX8/GOG-3024/innovaTV 205: addition of a new cohort using first-line tisotumab vedotin + pembrolizumab + carboplatin ± bevacizumab in recurrent/metastatic cervical cancer. (4th December 2022) - Vergote, Ignace; Mirza, Mansoor; Sehouli, Jalid; Lorusso, Domenica; Köse, Fatih; Cibula, David; Westermann, Anneke; Collins, Dearbhaile; Banerjee, Susana; Oaknin, Ana; Soumaoro, Ibrahima; Jain, Shweta; et al.
Abstract : Objectives: A 2-part, multicohort, phase 1b/2 trial, ENGOT-cx8/GOG-3024/innovaTV 205 (NCT03786081 ), established the recommended phase 2 dose (RP2D) and feasibility of tisotumab vedotin (TV) in combination with bevacizumab, pembrolizumab, or carboplatin (Monk et al, IGCS 2021). The current report details a new, ongoing, innovaTV 205 dose-expansion cohort evaluating combinations of TV, pembrolizumab, and carboplatin ± bevacizumab. Methods: The new cohort will include adult patients with recurrent or stage IVB squamous, adenosquamous, or adenocarcinoma of the cervix who received no prior systemic therapy and had an ECOG PS of 0 or 1. Patients will be treated with the RP2D of TV (2.0 mg/kg) + carboplatin (AUC 5 mg/mL), pembrolizumab (200 mg), and bevacizumab (15 mg/kg), or with TV + carboplatin (AUC 5 mg/mL) and pembrolizumab (200 mg), every 3 weeks. To assess the regimen's initial tolerability, a dose-limiting toxicity evaluation period will consist of completion of 1 treatment cycle of 21 days for 6 patients to receive the quadruplet combination. The primary end point is confirmed objective response per RECIST v1.1; secondary end points are duration of response, time to response, progression-free survival, overall survival, and safety. Enrollment is ongoing in the US and Europe, with additional sites planned globally. Results: Trial in progress: there are no available results at the time of submission. Conclusions: Trial in progress: there are no available conclusions at the time of submission. ©2022 American Society of Clinical Oncology, Inc. Reused with permission. This abstract was accepted and previously presented at the 2022 ASCO Annual Meeting. All rights reserved.